PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH SEKAM PADI SEBAGAI BAHAN BAKAR KOMPOR SEKAM YANG RAMAH LINGKUNGAN DI KINALI, PASAMAN BARAT - Ferry Lismanto Syaiful; Uyung Gatot S. Dinata; Yondra Hidayattullah (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
A stove is a tool used by the community to cook. The fuel used by the stove is LPG gas or kerosene, LPG gas. The scarcity of kerosene has occurred starting from a few years ago. At that time to get kerosene the people had to pay very expensive and even had to be willing to do a very long queue to get a few liters of kerosene. To anticipate this, we should think of alternative energy as a substitute for kerosene. This activity aims to provide a solution in overcoming the problem of pollution of rice husk waste as an environmentally friendly alternative energy through the manufacture of husk stoves to save fuel oil and gas KKN activities are held on 28 June to 8 August until September 2018. Number of students involved is 24 people. The form of activities carried out in the form of counseling, demonstration and training in making husk stoves by utilizing rice husks was carried out by Unand lecturers and KKN PPM Unand students by involving the community in Nagari Kinali Pasaman Barat. From this activity, the community was very enthusiastic and able to make husk stoves and process rice husk waste into the fuel of the husk stove. Besides that, husk stoves can be used by the community to cook in overcoming scarcity of kerosene as well as the utilization of rice husk waste as fuel. The stove is designed to burn rice husks using a limited amount of air for combustion which produces a blue luminous fire, which is almost similar to an LPG stove. From this activity, it is expected that the community can optimize the use of husk stoves in their daily lives to save costs and overcome the scarcity and high cost of LPG and kerosene as well as overcome environmental pollution from husk waste.